Booms, Crises, and Recoveries : A New Paradigm of the Business Cycle and its Policy Implications - Cerra, Valerie (IMF Working Papers; Working Paper ;, 2017)
All types of recessions, on average, not just those associated with financial and political crises (as in Cerra and Saxena, AER 2008), lead to permanent output losses. These findings have far-reaching conceptual and policy implications. A new paradigm of the business cycle needs to account for shifts in trend output and the puzzling inconsistency of output dynamics with other cyclical components of production. The 'output gap' can be ill-conceived, poorly measured, and inconsistent over time. Persistent losses require more buffers and crisis-avoidance policies, affecting tradeoffs in prudential, macroeconomic, and reserve management policies. The frequency and depth of crises are key determinants of long-term growth and drive a new stylized model of economic development.